Helicobacter pylori infection in patients with Barrett's oesophagus: a prospective immunohistochemical study. Issue 2 (February 1996) - Ricaurte, O; Fléjou, J F; Vissuzaine, C; Goldfain, D; Rotenberg, A; Cadiot, G; Potet, F
Abstract : The prevalence of Helicobacter pylori infection in patients with Barrett's oesophagus was studied prospectively. A sensitive immunohistochemical staining of H pylori was performed in oesophageal and gastric biopsies of 73 patients from a surveillance group with this condition. H pylori was detected in 11 cases of Barrett's mucosa (15%) and in 26 gastric mucosa specimens (35.6%). All cases positive in Barrett's mucosa were also positive in the stomach. In Barrett's oesophagus, H pylori was never found on specialised epithelium. The percentage of Barrett's mucosa showing inflammatory changes was similar in specimens with and without H pylori, both for chronic (81% v 79%) and acute (9% v 10%) infiltrates. These results indicate that H pylori infection does not play an aetiological role in Barrett's oesophagus and that colonisation of the metaplastic mucosa by this bacteria is related with the presence of gastric type mucosa in the oesophagus and of H pylori infection in the stomach.